Association of genotypes of biotransformation enzymes with susceptibility to chronic pulmonary tuberculosis - Maxim A. Alymenko; Ravil Sh. Valiev; Nail R. Valiev; Natalya P. Balobanova; Alexander V. Batishchev; Irina N. Tragira; Viacheslav A. Lipatov; Alexey V. Polonikov; Vladislav M. Kolomiets; Svetlana N. Volkova; Galina S. Mal; Vera A. Ragulina (ZAO "Consilium Medicum", 2024)
Background. Now it is well-known that the pulmonary tuberculosis is a multifactorial disease in which forming a certain role belongs as factors external the environment, and genetic to factors. Aim. In this study, the association of genes of xenobiotic biotransformation enzymes: NAT2 [590GA (rs1799930)], CYP2E1 [9896CG (rs2070676)], ABCB1 [3435TC (rs1045642)], GSTM1 (E/D) and GSTT1 (E/D) with susceptibility to torpid pulmonary tuberculosis was carried out. Materials and methods. 123 people suffering from torpid pulmonary tuberculosis were included in the study. Genomic DNA was isolated using Arrow Blood DNA 500 reagent kits from whole blood (at the NorDiag Arrow station). Next, the polymerase chain reaction was staged in real time using sets of reagents for SNPs genotyping. Results. The study showed an association of gene polymorphisms of xenobiotic biotransformation enzymes with susceptibility to torpid pulmonary tuberculosis, including certain clinical forms of pulmonary tuberculosis. Conclusion. During the conducted research it was established that implementation of results of genotyping of enzymes of biotransformation of xenobiotics in practice of the doctor of the phthisiatrician for the purpose of forming of risk groups of suffering from tuberculosis lungs which have a susceptibility probability to this disease that perhaps in the future will provide the individualized approach to prevention and treatment of these patients is necessary.